The Features of Socialization of Teenagers of Different Nationalities within Reference Groups - Chumicheva, Irina (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
The article presents the results of comparative analysis of the social integration of teenagers of different nationalities within their reference groups. Special aspects of social integration are determined by ethnic features, which makes it possible to take these features into account while preventing development problems of modern teenagers, decreasing the number of conflicts between different ethnic groups, living closely together, as well as while concerning ethnic, social and cultural aspects of modern multicultural society development.